Handbook of water and wastewater treatment plant operations - Spellman, Frank R. (CRC Press, Taylor & Francis Group, 2014)
Handbook of Water and Wastewater Treatment Plant Operations the first thorough resource manual developed exclusively for water and wastewater plant operators has been updated and expanded. An industry standard now in its third edition, this book addresses management issues and security needs, contains coverage on pharmaceuticals and personal care products (PPCPs), and includes regulatory changes. The author explains the material in layman's terms, providing real-world operating scenarios with problem-solving practice sets for each scenario. This provides readers with the ab.
Keywords: Water treatment plants -- Handbooks, manuals, etc.; Sewage disposal plants -- Handbooks, manuals, etc.; Water -- Purification -- Handbooks, manuals, etc.; Sewage -- Purification -- Handbooks, manuals, etc.; elektronické knihy; electronic books